Room temperature nanoparticulate interfacial layers for perovskite solar cells via solvothermal synthesis. Issue 38 (21st September 2017) - Savva, Achilleas; Papadas, Ioannis T.; Tsikritzis, Dimitris; Armatas, Gerasimos S.; Kennou, Stella; Choulis, Stelios A.
Abstract : Solvothermal synthesized CuO nanoparticles are implemented for the development of room temperature HTLs for highly efficient perovskite photovoltaics. Abstract : We present a solvothermal synthetic route to produce monodisperse CuO nanoparticles (NPs) in the range of 5–10 nm that can be used as a hole selective interfacial layer between indium tin oxide (ITO) and the perovskite active layer for p–i–n perovskite solar cells by spin casting the dispersions at room temperature. The bottom electrode interface modification provided by spherical CuO-NPs at room temperature promotes the formation of high quality perovskite photoactive layers with a large crystal size and strong optical absorption. Furthermore, it is shown that the nanoparticulate nature of the CuO hole transporting interfacial layer can be used to improve light manipulation within the perovskite solar cell device structure. The corresponding p–i–n CH3 NH3 PbI3 -based solar cells show high V oc values of 1.09 V, which is significantly higher compared to the V oc values obtained with conventional PEDOT:PSS hole selective contact based perovskite solar cells.